A Study of Contrasts in Balkrishna Sama’s Prahlad - Adhikari, Shreedhar (Academia Research Journal, 2023)
Contrast is considered as a powerful tool that researchers used to identify and describe differences they encounter in the world. It is a literary device that explores differences between two or more things, ideas, and persons. It is also used to evaluate differences. The present study makes an attempt to examine contrasts as literary device in Balkrishna Sama’s drama, Prahlad. The purpose of this study is to explore a cultural/social contrast that has been expressed through speech and action of the characters as Hiranya Kashyapu and Prahlad. The contrast is used in literary works in order to emphasise on intended meaning of literary works. Qualitative research methodology has been used for the study. The original text, Prahlad, has been primarily analysed using the technique of social/cultural contrast. As a supportive technique, antithesis has also been used. The close textual analysis has shown many layers of contrasts in the drama. Analysis reveals the significant role of literary contrasts in portraying interaction between characters and their surroundings including human beings, nature, and society. Tracing the contrasting personalities and perspectives of the characters, one can discern a variety of messages about human experiences. Of special significance is Sama’s skill in showing how interaction between Hiranya and Prahlad reveal true nature of human beings, nature and society. The contrast used in the play, Prahlad sends strong messages of thinking spiritually and materially. There is struggle between spiritualism and materialism, religion and science, path of devotion and thirst of temporal, service and business and so on. The study has highlighted on new approach of interpreting to the ancient literature.